Avaliação da atividade antifúngica, molecular docking e citotoxicidade do óleo essencial de vitex gardneriana shauer frente cepas de Candida albicans - Barros, Amanda de Lima (2025)
Infections caused by Candida albicans, a clinically important yeast-like fungus, have become a growing public health problem, particularly due to increasing resistance to available antifungals. Given this scenario, the search for more effective, affordable, and less adverse therapeutic alternatives is urgently needed. Brazil, in turn, boasts a broad plant biodiversity, including species used by traditional communities, such as Vitex gardneriana Schauer, an aromatic and medicinal plant with recognized antimicrobial, antioxidant, and larvicidal properties. Although promising, this species still lacks studies against clinical strains of C. albicans. Given the above, this study aims to analyze the antifungal and synergistic potential and chemical composition of the essential oil obtained from the botanical species V. gardneriana against clinical strains isolated from samples from the Santa Casa de Misericórdia Hospital in Sobral, Ceará. It also aims to obtain the cytotoxicity profile and determine the interaction of the constituents of V. gardneriana oil with proteins from the pathogen C. albicans. Antifungal activity was assessed by broth microdilution, yielding an MIC of 5 mg/mL for all strains. A synergistic effect was observed when combined with amphotericin B, reducing the inhibitory concentration of the essential oil by more than 30-fold. Antioxidant activity (DPPH method) showed an IC50 of 85.86 mg/mL, while hemolytic assays in human erythrocytes showed an IC50 of 20 mg/mL. Molecular docking revealed greater affinity of EO compounds with Sap5 (-7.3 kcal/mol) than with Als3 (-6.2 kcal/mol), with some ligands (e.g., 1-epi-cubenol, caryophyllene oxide) binding to different regions of Amphotericin B. The essential oil of Vitex gardneriana Shauer (OEVG) proved to be an important finding for science, as it presented antifungal activity, a synergistic effect with Amphotericin B, low cytotoxicity, and antioxidant activity. Furthermore, the data found suggest a possible synergistic effect of the ligands on the control profile of Amphotericin B. Therefore, it is essential to carry out in vivo and clinical trials in order to confirm the efficacy and pharmacological safety of the compounds analyzed.